Short-Time Work and Precautionary Savings - Thomas Dengler; Britta Gehrke (Institute of Labor Economics (IZA), 2021)
In the Covid-19 crisis, most OECD countries use short-time work schemes (subsidized working time reductions) to preserve employment relationships. This paper studies whether short-time work can save jobs through stabilizing aggregate demand in recessions. We build a New Keynesian model with incomplete asset markets and labor market frictions, featuring an endogenous firing as well as a short-time work decision. In recessions, short-time work reduces the unemployment risk of workers, which mitigates their precautionary savings motive and aggregate demand falls by less. Using a quantitative model analysis, we show that this channel can increase the stabilization potential of short-time work over the business cycle up to 55%, even more when monetary policy is constrained by the zero lower bound. Further, an increase of the short-time work replacement rate can be more effective compared to an increase of the unemployment benefit replacement rate.
Keywords: E21; E24; E32; E52; E62; J63; 330; short-time work; fiscal policy; incomplete asset markets; unemployment risk; matching frictions